Which factors may affect the willingness to take the HIV test? A research on Italian adults’ sample. - Mancini, Tiziana; Foà, Chiara (Acta Biomedica Atenei Parmensis, 2013)
Background and aim. Why people do not take the HIV test? The literature on the health-related behaviors associated with HIV infection has highlighted the role played by socio-demographical, behavioral, and cognitive variables. Less often has been studies the impact of psychosocial and normative factors that can affect willingness to test HIV. The aim of this study was to investigate which were the main psycho-social factors that promote/inhibit the intention to take the HIV test. Method. A questionnaire was submitted to a sample of 775 Italian adults (50. 7% female; mean age = 37.24; SD = 10.94; range 17 - 66 years). Results. Logistic Regression Analysis shown that age, risk behaviors, and personal concern are significantly predictors of the intention even if a positive attitude towards HIV test is the strongest predictor. Results showed also that the normative component of attitude (perception of social disapproval) and emotional component (shame and embarrassment) discouraged people from taking the test, while the cognitive-rational component did not. Conclusions. Are the perception of social disapproval by "significant others" and the social emotions of shame and embarrassment that discourage people from taking the test. Implications will be discussed.